2006
DOI: 10.1111/j.1464-410x.2006.06129.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression and survival in patients with prostate carcinoma and positive lymph nodes after radical retropubic prostatectomy

Abstract: pathological stage, number of positive lymph nodes and hormone therapy after RP. The statistical assessment included univariate regression analysis, and to analyse the distribution of clinical findings in different groups, Mantel-Haenszel statistics were used to test for differences in the numbers of patients. Survival and progression-free interval were assessed by Kaplan-Meier estimates and differences between groups calculated by log-rank statistics and Cox regression models. RESULTSThe median (range) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The biomarkers discussed in this section warrant further investigation in prediction of lymph-node metastasis and clinical management of prostate cancer [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109]. We refer the reader to the Supplementary Material to have a complete list of probes and their correlations with the Information Theory quantifiers.…”
Section: Resultsmentioning
confidence: 99%
“…The biomarkers discussed in this section warrant further investigation in prediction of lymph-node metastasis and clinical management of prostate cancer [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109]. We refer the reader to the Supplementary Material to have a complete list of probes and their correlations with the Information Theory quantifiers.…”
Section: Resultsmentioning
confidence: 99%
“…(1983) [11] 1975-81 10/13 13/42 Kramolowsky et al . (1984) [12] 1969 especially when supplemented with adjuvant hormone therapy, offer an excellent local control of the disease as well as overall and progression-free survival in the long term [16][17][18]. Considering these data, the concept of performing FS on PLNs may become irrelevant, as RP and PLND will be performed for both therapeutic as well as staging purposes regardless of the status of the PLNs during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the preadjuvant androgen deprivation therapy (ADT) era, 10-year PSA recurrence-free, clinical recurrence-free, and overall survival were 40, 69, and 74%, respectively, among 163 patients with N+ disease who received no adjuvant or neoadjuvant therapy. 104,105,[114][115][116] Boorjian et al observed that a single nodal metastasis had an approximately threefold significant increase in disease progression, and that ≥2 nodes imparted an additional twofold risk in a cohort of 507 node-positive patients of which the vast majority received adjuvant ADT. However, nodal metastases remain a poor prognostic factor with 10-year event-free survival for patients with positive VI.…”
Section: Association Of Nodal Metastases and Clinical Outcomesmentioning
confidence: 99%